Morality in the Philosophy of Thomas Hobbes Cases in the Law of Nature - Lloyd, S. A (Cambridge University Press, 2013)
This is a book about Hobbes’s moral philosophy. It examines his “Laws of Nature” because Hobbes insisted that “the science of them is the true and onely moral philosophy”.1 Hobbes terms the conclusions of moral philosophizing once Laws of Nature have been brought to bear on specific practical questions “cases in the law of nature”, hence the book’s title.